Meat characteristics of red jungle fowl, Malaysian village chicken and commercial broiler - Idris, Lokman Hakim; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Mohamed Mustapha, Noordin; Sazili, Awis Qurni (2012)
This study was conducted to compare the meat characteristics of Red jungle fowl, Malaysian village chicken and the commercial broiler at different age. The three different breeds of chickens were sacrificed at days 20, 56 and 120 post-hatch. The collagen composition, pH, cooking loss and shear force value in Red jungle fowl and Malaysian village chicken were higher than the commercial broiler. The meat of Red jungle fowl and Malaysian village chicken were more reddish and lighter than the commercial broiler.